Freedom of expression - Stearman, Kaye (Wayland Hove, 1993)
Freedom of Expression" by Kaye Stearman is a 48-page hardcover book published in 1993. It examines the Universal Declaration of Human Rights adopted in 1948, focusing on how this declaration is abused throughout the world. The book is illustrated with color and black-and-white photographs